Hydrophilic graphene quantum dots as turn-off fluorescent nanoprobes for toxic heavy metal ions detection in aqueous media. (November 2021) - Anusuya, T.; Kumar, Veeresh; Kumar, Vivek
Abstract: Efforts are being made to develop fast, cost-effective and sensitive sensor to detect water contamination by toxic heavy metal ions. The oxygenated functional groups decorated graphene quantum dots (GQDs) effectively enhances the aqueous solubility and considered as a more desirable and simple sensing material with high sensitivity. Here, photoluminescence (PL) property of GQDs has been employed to devise an optical nanosensor for the detection of toxic heavy metal ions in aqueous media. Hydrothermal method was employed to synthesize highly fluorescent and water soluble GQDs. The fluorescence intensity reduces with the increase in toxic heavy metal ions concentration. The observed PL was analyzed by the Stern-Volmer equation to study the fluorescent quenching mechanism of the system. Nonlinear behavior of Stern-Volmer plot suggests that the reduction in the fluorescent intensity is due to the combination of dynamic and static processes. The fluorescence quenching results showed that, the as synthesized GQDs are an efficient fluorescent probe for heavy metal ions viz. Hg 2+, Cd 2+ and Pb 2+ with the detection limit of 1.171 μM, 2.455 μM and 2.011 μM respectively. This study shows the viability of GQDs as promising material for sensing the heavy metal ions in aqueous solution. Graphical abstract: Image 1 Highlights: Optical nano sensor for the detection of heavy metal ions is devised using GQDs. Highly fluorescent and hydrophilic GQDs are synthesized by Hydrothermal method. PL is analyzed by the S–V plot to study the fluorescent quenching mechanism. Dynamic and static processes are involved in quenching.